Properties of Functions Involving Struve Function - Mosiun, Jonathan; Halim, Suzeini Abd (MDPI, 2018)
Let f (z) = z + ∑n=2 ∞ anzn and gp,b,c(z) = z + ∑n=2 ∞ (-c4)n-1/(3/2)n-1(k)n-1zn with p, b, c ∈ C, k = p + b+2/2 ≠ 0,-1,-2, . . . be two analytic functions in the unit disk U = (z:|z| < 1). This paper gives conditions so that the function Tp,b,c(z) = ( f * g)(z), a function associated with the Struve function, is univalent, starlike, or convex in the unit disk.